ASSESSING THE QUALITY OF HEALTHCARE SERVICES: A THEORETICAL ASPECT - Pryimak, Liubomyr (Public Management and Policy, 2025)
In the XXI century, in the field of healthcare, the emphasis has shifted to innovation, technological development, and active involvement of patients in assessing the quality of medical services. This process requires an in-depth analysis of the factors that affect the provision of quality services and effective management of the health care system, which complicates the unification of standards. The purpose of the study is to analyze the main components of the quality of medical services in modern conditions. The features of the criteria for assessing the quality of medical services are defined and given: technical competence (competence of employees who provide medical services); material and living conditions; access to services (determined by the availability of services to different segments of the population in different territories of residence); interpersonal relationships in the process of providing services (information and consulting work, quality of medical service and communication with patients); continuity (continuity of service provision, speed and completeness and timeliness of services provided to patients); efficiency (measured both by economy and low cost, as well as by the optimality of using all types of resources in the provision of services); safety (safety for patients, the environment, medical personnel, compliance with waste disposal measures and non-contamination of employees, compliance with sanitary and hygienic conditions). It has been proven that comprehensive compliance with the defined criteria will ensure high efficiency of medical services, their accessibility for the population and generally improve the quality of life of the population. It has been proven that comprehensive compliance with and monitoring of certain criteria allows for ensuring high-performance medical services, their accessibility for the population and generally improves the quality of life. The quality criteria used for monitoring must be meaningful, specific, sensitive and reliable in order to ensure the effectiveness of management decisions.